POTENSI DAN STRATEGI PENGEMBANGAN KAMPUNG FLORY SEBAGAI KAWASAN WISATA BERBASIS MASYARAKAT - Achmad Septio; Tuti Karyani (Universitas Tadulako, 2020)
Kampung Flory is an agro-tourism area in Sleman Regency. The Community Based Tourism (CBT) concept is being used to guide the management and development of Kampung Flory. Potential attractions are quite diverse including nature, outbound activities, and rural culinary specialties. Developing Kampung Flory requires a strategy to increase its potential with positive impactsfor the local community. The purpose of this research was to identify and evaluate the potential attractions in Kampung Flory and appropriate CBT development strategies. This qualitative research adopted a case study approach with AHP (Analytical Hierarchy Process) analysis. Data were collected through observation and interviews. Informants were selected purposively, due to time limitations, and involved 8 people who were deemed particularly knowledgeable regarding Kampung Flory. The analysis showed sub-optimal exploitation of potential CBT assets and agro-tourism development in the Kampung Flory area. The main causal factor was weaknesses in the quality and quantity of human resources, in particular a lack of understanding on how to respond to internal and external factors. The strategy alternative required is to improve the quality of human and institutional resources related to foreign language skills, managerial training and organization of tourism management, and mastery of technology in order to develop and maximize the CBT potential of this area. Keywords: Agro-tourism, AHP (Analytical Hierarchy Process), CBT (Community Based Tourism), Development Strategy, and Sleman Regency.